Between Hammers and Anvils: the Socialization of European Permanent Representatives Romania and Bulgaria – a comparative Case Study - Neculai-Cristian Şurubaru (Romanian Journal of European Affairs, 2010)
The question of administrative governance in the European Union reflects the links between the decision-making process and the national Member States. The Permanent Representations are the key institutions translating Brussels policies into the national sphere. This article contradicts the constructivist/Europeanization arguments for thick socialization of permanent representatives and focuses on Romania and Bulgaria, in the institutional medium of the Political and Security Committee. The author claims that the adaptation – thin socialization – of the permanent representatives can be measured differently, within a theoretical framework based on intergovernmentalism, institutionalism and „Brusselization”. Specific for the Bulgarian representatives is their slow pace in acquiring the formal and informal procedures of the committee, while the Romanian diplomats have a different relation with their Ministry of Foreign Affairs. Both countries are similar in terms of networking and their logic is driven by national interests. It is important to look at these countries as a potential model of comparison between Member States, in how they integrate in the multi-level diplomatic layers in Brussels.